The Conversational Interface Talking to Smart Devices - McTear, Michael; Callejas, Zoraida; Griol, David (Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive introduction to the conversational interface, which is becoming the main mode of interaction with virtual personal assistants, smart devices, various types of wearables, and social robots. The book consists of four parts: Part I presents the background to conversational interfaces, examining past and present work on spoken language interaction with computers; Part II covers the various technologies that are required to build a conversational interface along with practical chapters and exercises using open source tools; Part III looks at interactions with smart devices, wearables, and robots, and then goes on to discusses the role of emotion and personality in the conversational interface; Part IV examines methods for evaluating conversational interfaces and discusses future directions. · Presents a comprehensive overview of the various technologies that underlie conversational user interfaces; · Combines descriptions of conversational user interface technologies with a guide to various toolkits and software that enable readers to implement and test their own solutions; · Provides a series of worked examples so readers can develop and implement different aspects of the technologies.